Dietary habits in three Central and Eastern European countries: the HAPIEE study - Boylan, Sinéad; Welch, Ailsa; Pikhart, Hynek; Malyutina, Sofia; Pajak, Andrzej; Kubinova, Ruzena; Bragina, Oksana; Simonova, Galina; Stepaniak, Urszula; Gilis-Januszewska, Aleksandra; Milla, Lubomíra; Peasey, Anne; et al. (BMC public health, 2009)
BACKGROUND: The high cardiovascular mortality in Eastern Europe has often been attributed to poor diet, but individual-level data on nutrition in the region are generally not available. This paper describes the methods of dietary assessment and presents preliminary findings on food and nutrient intakes in large general population samples in Russia, Poland and the Czech Republic. METHODS: The HAPIEE (Health, Alcohol and Psychosocial factors In Eastern Europe) study examined random samples of men and women aged 45-69 years at baseline in Novosibirsk (Russia), Krakow (Poland) and six Czech urban centres in 2002-2005. Diet was assessed using a food frequency questionnaire (at least 136 items); complete dietary information was available for 26,870 persons. RESULTS: Total energy intakes among men ranged between 8.7 MJ in the Czech sample and 11.7 MJ in the Russian sample, while among women, energy intakes ranged between 8.2 MJ in the Czech sample and 9.8 MJ in the Russian sample. A Healthy Diet Indicator (HDI), ranging from a score of 0 (lowest) to 7 (highest), was developed using the World Health Organisation's (WHO) guidelines for the prevention of chronic diseases. The mean HDI scores were low, ranging from 1.0 (SD = 0.7) among the Polish subjects to 1.7 (SD = 0.8) among the Czech females. Very few subjects met the WHO recommended intakes for complex carbohydrates, pulses or nuts; intakes of saturated fatty acids, sugar and protein were too high. Only 16% of Polish subjects met the WHO recommendation for polyunsaturated fat intake. Consumption of fruits and vegetables was lower than recommended, especially among those Russian subjects who were assessed during the low intake season. Fewer than 65% of subjects consumed adequate amounts of calcium, magnesium and potassium, when compared with the United Kingdom's Reference Nutrient Intake. CONCLUSION: This first large scale study of individual-based dietary intakes in the general population in Eastern Europe implies that intakes of saturated fat, sugar and complex carbohydrates are a cause for concern. The development of country-specific nutritional tools must be encouraged and nutritional campaigns must undergo continuing development.
Keywords: průzkumy a dotazníky; Female; energetický příjem; ženské pohlaví; Surveys and Questionnaires; Diet Surveys; lidé; Energy Intake; dieta; Humans; Risk Factors; Diet; Male; dieta - přehledy; Aged; Cardiovascular Diseases; Czech Republic; Socioeconomic Factors; Russia; index tělesné hmotnosti; rizikové faktory; kardiovaskulární nemoci; Česká republika; lidé středního věku; socioekonomické faktory; senioři; mužské pohlaví; Poland; Body Mass Index; Middle Aged; Rusko; Polsko